Abstract Painting Art Study Yasrul Sami's Expressionism - Rian Ramadhan; Agusti Efi (UNIVERSITAS PAKUAN, 2026)
This study aims to describe and analyze Yasrul Sami's abstract expressionist paintings systematically, factually, and accurately, including aspects of symbols, meanings, techniques, and characteristics. The study uses a qualitative approach with a descriptive analysis type, based on Edmund Burke Feldman's theory which includes four stages of artwork analysis: description, analysis, interpretation, and evaluation. This study uses a qualitative approach with a descriptive analysis research type, aiming to explain systematically, factually, and accurately Yasrul Sami's abstract expressionist paintings. The study was conducted in Padang City, West Sumatra, specifically in the painting studio of Padang State University and SMKN 4 Padang, in the period July–September 2025. Data were obtained from two main sources, namely primary data from Yasrul Sami as the core informant, as well as secondary data in the form of documentation of work catalogs, interviews with other artists, fine arts lecturers, teachers of SMKN 4 Padang, and related exhibition documents. The findings show that Yasrul Sami utilizes mixed media techniques, impasto, layering, plakat, and dripping, with a combination of dark and bright colors that create texture, depth, and symbolize emotions, self-reflection, and social dynamics. His works emphasize struggle, introspection, hope, and the human connection to life experiences. The research findings emphasize the importance of exhibitions, cultural education, and digital publications to increase public appreciation of art, introduce local artists, and strengthen Minangkabau cultural identity.